Metallic materials properties development and standardization (MMPDS) : ‡b MMPDS-12, July 2017. (Battelle Memorial Institute, 2017)
The Metallic Materials Properties Development and Standardization (MMPDS) Handbook is an accepted source for metallic material and fastener system allowables, recognized by the Federal Aviation Administration (FAA), all departments and agencies of the Department of Defense (DoD), and the National Aeronautics and Space Administration (NASA), within the limitations of the certification requirements of the specific government agency. 2017 saw the release of MMPDS-12, superseding MMPDS-11 and prior editions of the MMPDS, as well as all editions of its predecessor MIL-HDBK-5. The MMPDS Handbook is revised regularly to ensure that reliable, statistically-based design properties are available for as many mature materials and/or product forms as possible. Changes specific to this version, MMPDS-12, include: * Revision of modulus (chapter 5) * Re-evaluation of some fatigue curves (chapter 6) * Update of shear strength basis footnotes (chapter 8) * Changes in strain rate requirement for full range stress-strain curves (chapter 9) * Calculations of modulus for stress-strain curve analysis (chapter 9)--Provided by publisher.